Management of Persistent Pupillary Membrane Presenting with Strabismus - Bülbül, Mustafa; Erdag, Murat (My University, 2026)
In this study, we report a case of a 4-year-old male patient who presented with persistent pupillary membrane (PPM) in the right eye, accompanied by secondary deprivation amblyopia and esotropia. PPM is a congenital ocular anomaly resulting from remnants of the anterior tunica vasculosa lentis. While these membranes typically regress spontaneously within the first year of life, persistent cases may obstruct the visual axis and cause significant visual problems. If left untreated, PPM can lead to various types of amblyopia, including deprivation, strabismic, or anisometropic amblyopia. In our patient, the persistent membrane resulted in visual deprivation, contributing to the development of amblyopia and ocular misalignment. Early diagnosis and intervention are crucial to prevent long-term visual impairment in similar cases. This report aims to highlight the importance of careful ophthalmologic evaluation in infants with PPM to ensure timely management and prevent amblyogenic effects.
Keywords: Göz Hastalıkları